Radical decomposition of hydrogen peroxide catalyzed by iodide for degradation of organic dyes - Naiara Miotto Menino; Paloma Truccolo Reato; Carolina Elisa Demaman Oro; Luciana Dornelles Venquiaruto; Rogério Marcos Dallago; Marcelo Luis Mignoni (The Journal of Engineering and Exact Sciences)
The decomposition of hydrogen peroxide into hydroxyl radical, a powerful oxidizing agent, has aroused the interest of the scientific community due to the numerous possible applications, mainly in the treatment of effluents. In this work, the potential of using iodide ions as precursors of the hydroxyl radical was evaluated. Iodide, in addition to being theoretically viable, simultaneously leads to the production of molecular iodine, which also has an oxidizing characteristic, and can contribute to the efficiency of the process. The results demonstrated that iodide ions act by promoting the radical decomposition of H2O2 and that the process is dependent on the pH of the reaction medium, with the generation of radical hydroxyl only manifesting itself at pH 2.5 and 3.0. The removal results proved that the anionic or cationic nature of the dye interferes with the reaction mechanism. For methylene blue, a cationic dye, a small portion of TOC was removed by oxidation (7.9 to 20.6%) and the remainder occurred by adsorption (79.4 and 92.1%). The interaction of methylene blue with the surface of molecular iodine prevents its contact with the iodide ions present in the reaction medium, allowing it to remain in a solid state in solution and act as an adsorbent, contributing to better efficiency. For the tartrazine yellow dye, an anionic dye, there was no formation of solid iodine, indicating the absence of an adsorptive process, with the oxidation mechanism, showing removal of 11.3 to 18.9%, similar to the results found for the removal of blue. methylene by oxidation.